Asymmetry in catalysis: 'unidirectional' amino acid racemases. (22nd January 2021) - Bearne, Stephen L.
Abstract : d -Amino acids play widespread structural, functional and regulatory roles in organisms. These d -amino acids often arise through the stereoinversion of the more plentiful l -amino acids catalysed by amino acid racemases and epimerases. Such enzymes are of interest since many are recognized targets for the development of drugs or may be employed industrially in biotransformation reactions. Despite their enzyme–substrate complexes being diastereomers, some racemases and epimerases exhibit a kinetic pseudo-symmetry, binding their enantiomeric or epimeric substrate pairs with roughly equal affinities and catalyzing their stereoinversion with similar turnover numbers. In other cases, this kinetic pseudo-symmetry is absent or may be 'broken' by substitution of a catalytic Cys by Ser at the active site of cofactor-independent racemases and epimerases, or by altering the Brønsted base of the catalytic dyad that facilitates deprotonation of the Cys residue. Moreover, a natural Thr-containing l -Asp/Glu racemase was discovered that catalyses 'unidirectional' substrate turnover, unlike the typical bidirectional racemases and epimerases. These observations suggest that bidirectional Cys–Cys racemases may be re-engineered into 'unidirectional' racemases through substitution of the thiol by a hydroxyl group. Catalysis by such 'unidirectional' racemase precursors could then be optimized further by site-directed mutagenesis and directed evolution to furnish useful enzymes for biotechnological applications.